Development of an adaptive video streaming in heterogeneous networks - Issa, Sinzobakwira (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The developments and rapid growth of smartphones and other electronic gadgets have opened a new era of data traffic. According to Sisco, video traffic itself now is estimated to occupy more than 75 percents of data traffic. Researchers have contributed a lot in this area of video streaming. There are many challenges when it comes to deliver quality videos especially for mobile users. The major problem is that, the bandwidth which works well now may not be working sometimes later. This therefore complicates the distribution of the bandwidths for users by ISPs. So many researches focus on system delivery. However users have their own demands for the videos to be perceived. Those users' demands are usually volatile. They can dynamically change their demands by requesting to view the video with high resolutions. As such, it is extremely challenging to mitigate system demands and users with heterogeneous needs for perceiving satisfactory video quality. This dissertation deals with the design of an effective video streaming for users with demand heterogeneity in terms of quality. To reduce part of those challenges, this dissertation, through the algorithm proposed, it firstly tackles the scalability issue as it is one of the constraints in video streaming. It gives the overview architecture of scalable video coding for adaptive quality. It underlines the selection of different layers of adaptive video and the type of block to be selected in order to stream the videos with satisfactory quality to viewers. Secondly, the design also highlights two main parts of the system bandwidth rescaling. The bandwidth resizing is basically subdivided into two subsections; one part consider resizing system based on adaptive streaming system and the other side peer cooperation as well as the support offered by users. Linear programing is also design as an optimization strategy to resolve the problem of users' demands of video streaming quality in heterogeneous system. It is basically a trade-off between bandwidth and users' demand in terms of quality. High Fanout Protocol (HFP) can serve 17 % to 50% more subscribers than Greedy, Centralized, and Snow-ball approaches for large numbers subscribers with delay-bounded video. The algorithms developed show that the perceptual users' quality is improved, playback delay is reduced and bandwidth consumption is minimized. The system uses mesh overlay and future researches could also considered other forms as well such tree or cloud, or mixture of two.